RESULTS OF A STUDY OF THE INFLUENCE OF CHANGES IN OILS CHARACTERISTICS ON WEAR OF DIESEL AND GAS ENGINE CYLINDER LINERS - Utaev, Sobir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Research on changes in the characteristics of oil in diesel and gas engines based on diesel. During the research, the laws of lubrication theory, methods of planning experiments and mathematical statistics, as well as methods based on existing regulatory documents were used. When processing experimental data, processing methods using Microsoft Office Excel application packages were used. The alkaline number in samples of used oils varies from 2.24 to 1.4, which indicates the emergency condition of the used oil. The results of analyzes of the alkaline number of the studied motor oils show that when the engine is running on gaseous fuel it decreased on average from 6.0 to 2.24 mg KOH/g, and when running on diesel fuel from 6.0 to 1.4 mg KOH/g g i.e. below the permissible level. According to the research results, we can say that in gas diesel engines, the content of mechanical impurities is less compared to diesel, the alkalinity after operation of 500 engine hours is closer to the maximum value of 2.24, the oil viscosity decreases insignificantly and after 500 engine hours is 9.3 mm2 /s, the oil service life increases by an average of 25%; in diesel engines, one of the main oil indicators, alkalinity and kinematic viscosity, are below acceptable values.